Deuterium in marine organic biomarkers: toward a new tool for quantifying aquatic mixotrophy. Issue 3 (4th March 2022) - Cormier, Marc‐André; Berard, Jean‐Baptiste; Bougaran, Gaël; Trueman, Clive N.; Mayor, Daniel J.; Lampitt, Richard S.; Kruger, Nicholas J.; Flynn, Kevin J.; Rickaby, Rosalind E. M.
Summary: The traditional separation between primary producers (autotrophs) and consumers (heterotrophs) at the base of the marine food web is being increasingly replaced by the paradigm that mixoplankton, planktonic protists with the nutritional ability to use both phago(hetero)trophy and photo(auto)trophy to access energy are widespread globally. Thus, many 'phytoplankton' eat, while 50% of 'protozooplankton' also perform photosynthesis. Mixotrophy may enhance primary production, biomass transfer to higher trophic levels and the efficiency of the biological pump to sequester atmospheric CO2 into the deep ocean. Although this view is gaining traction, science lacks a tool to quantify the relative contributions of autotrophy and heterotrophy in planktonic protists. This hinders our understanding of their impacts on carbon cycling within marine pelagic ecosystems. It has been shown that the hydrogen (H) isotopic signature of lipids is uniquely sensitive to heterotrophy relative to autotrophy in plants and bacteria. Here, we explored whether it is also sensitive to the trophic status in protists. The new understanding of H isotope signature of lipid biomarkers suggests it offers great potential as a novel tool for quantifying the prevalence of mixotrophy in diverse marine microorganisms and thus for investigating the implications of the 'mixoplankton' paradigm.